Impact of Health Education on Knowledge and Awareness of Multidrug-Resistant Tuberculosis in Banyumas Regency, Indonesia - Octaviana, Devi; Wijayanti, Siwi; Nurlaela, Sri (Universitas Ahmad Dahlan, 2019)
Background: The increased case of multidrug-resistant tuberculosis (MDR-TB) in the community required more prevention efforts to reduce the cases. Lack of knowledge and awareness in the community could be one of the causes of this problem. The study aimed are to analyse the effectiveness of health education to increase knowledge and awareness of people to MDR-TB. Methods: A quasi-experiment study with one-group pretest-and posttest design was used in this study. 32 respondents were included in this study with exclusion and inclusion criteria. Intervention carried out in the form of counselling to respondent for 1.5 hours with additional methods such as leaflets, modules and posters. Results: This study showen that health education could improve knowledge (5.45%) and awareness (3.59%) of participants about MDR-TB. Based on bivariate analysis, it is showed that there were no significant differences in knowledge of respondents pre and post-intervention however, there were significant differences in awareness of respondent. Conclusion: This study recommended the implementation of health education more intensively to the community about MDR-TB. The application of various media in health education was also important to improve transfer knowledge to the community. Improvement of knowledge and awareness of people about MDR-TB was a crucial aspect to conduct effective prevention effort of this disease. Keywords: tuberculosis; multi-drug; resistant